Effect Of Abdominal Streaching Therapy And Pelvic Rocking Exercise That Experience Primary Dysmenor In Adolescent Girls - Faridah, Virgianti Nur; Susanti, Inta; Nisa', Firotin (Universitas Muhammadiyah Lamongan, 2022)
Background: Primary dysmenorrhea can interfere with daily activities and a symptomatic phenomenon includes abdominal pain, cramps and back pain that occurs during menstruation. One of the nonpharmacological treatments is abdominal stretching and pelvic rocking exercise.Objectives: The purpose of the study was to determine the effect of abdominal stretching and pelvic rocking exercise on changes in primary dysmenorrhea pain in young womenDesign: The research design used is pre-experimental. The population in this study was young women with primary dysmenorrhea, with a large random sampling technique of 47 or samples that influenced the inclusion criteria. Independent variables of combination therapy Abdominal stretching and pelvic rocking exercise, dependent variables primary dysmenorrhea. Data was collected using the Numeric Rating Scale (NRS) instrument.Results: The patient's pain level before treatment was 68.1% experienced moderate pain. The pain felt by the patient after treatment was 49.5%. Wilcoxon's statistical test showed a value of Ï value of 0.000< Î± 0.05 so that there was an influence of abdominal stretching and pelvic rocking exercise on primary dysmenorrhea in young womenConclusions: Based on the results of the study, the combination therapy of abdominal streaching and pelvic rocking exercise can be used as complementary therapy in primary dysmenorrhea.